2012
DOI: 10.1002/jsfa.5806
|View full text |Cite
|
Sign up to set email alerts
|

High‐anthocyanin strawberries through cultivar selection

Abstract: The new breeding line BL 2006-221 has the potential to be used in the development of phytochemically rich strawberry cultivars. Using hue angle as a screening tool for total anthocyanin concentration and extraction of anthocyanins from strawberries by ASE at 40 °C would support such cultivar development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 51 publications
4
38
1
1
Order By: Relevance
“…Overall, there was considerable (P < 0.001) variability due to the main effects (year, harvest date, genotype, and storage time) and their interactions on the TAC content of strawberry fruit. Several studies have previously shown that anthocyanin content varies significantly with the year, harvest date and genotype (Fredericks et al, 2012;Pozo-Insfran et al, 2006;Singh et al, 2011;Tulipani et al, 2011). The annual climactic changes during the season may result in different TAC accumulation patterns whereas specific genotype characteristic (e.g., surface color) are highly correlated with the TAC content of strawberries (Nunes, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, there was considerable (P < 0.001) variability due to the main effects (year, harvest date, genotype, and storage time) and their interactions on the TAC content of strawberry fruit. Several studies have previously shown that anthocyanin content varies significantly with the year, harvest date and genotype (Fredericks et al, 2012;Pozo-Insfran et al, 2006;Singh et al, 2011;Tulipani et al, 2011). The annual climactic changes during the season may result in different TAC accumulation patterns whereas specific genotype characteristic (e.g., surface color) are highly correlated with the TAC content of strawberries (Nunes, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Anthocyanin content in strawberry fruit is highly correlated with the color of the fruit. Thus, color has been considered a good screening tool for high anthocyanin strawberries in breeding programs (Fredericks et al, 2012;Nunes, 2015), though the dark color is often undesirable in commerce due to the perception that dark fruit are overripe.…”
mentioning
confidence: 99%
“…Anthocyanins do not just improve tolerance to grey mould but also provide health benefits (Terry et al , ). Breeding for higher anthocyanin content in strawberries is possible and facilitated by existing variation in the germplasm (Fredericks et al , ; Jing, ). Inducing anthocyanin accumulation in flowers could also help to limit flower infections.…”
Section: Looking Into the Future: Improving Strawberry Resistance To mentioning
confidence: 99%
“…It is also common to find applications in which the sample is re-extracted several consecutive times, in order to fully extract the target compounds. This strategy was shown to be useful to extract anthocyanins from strawberry [95], sweet potato [102] and grape skins [112], phenolic acids from food industry byproducts [96], flavonoids from spinach [118] or alkaloids [128], among others, performing 3 consecutive static extraction cycles.…”
Section: Applicationsmentioning
confidence: 99%